Demographic Risk Factors for Mortality of Covid 19 Patients Admitted in A Tertiary Care Hospital: A Cross-Sectional Study - Singh, Sandhya; Mishra, Shraddha; Dubey, Shubhra (National Journal of Community Medicine, 2022)
Context/Background: During the COVID-19 pandemic, government worldwide imposed severe restrictions on public life to limit its spread. For informed decision making it is important to quantitatively assess how the age, gender, and length of stay affects mortality of COVID 19 patients. It is important to find out more useful prognostic factor for mortality. This study revealed prevalence of mortality across age, gender, and length of stay and assessed determinants of mortality using independent variable age, gender, and length of stay. Methodology: A Cross-sectional observational study was conducted on 3084 Covid 19 positive patients admitted during April 2020 to June 2021 at Bundelkhand Medical College Sagar. Results: In this study mortality occurred in 510 patients. Age group analysis presented that majority of patients died in 60–74-year age group whereas maximum patients who died are having length of stay for 0-7 days, whereas gender has no significant role. There was significant influence of age group and length of stay on the mortality of Covid-19 positive patients (χ2(9) =495.30, P<.001). Conclusions: Mortality of covid positive patients being impacted by demographic risk factors like age group, length of stay.